2011
DOI: 10.1007/s15010-011-0126-4
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of potential biomarkers for the discrimination of bacterial and viral infections

Abstract: From the novel potential biomarkers, only PCT demonstrated superiority over the routine parameters in the differentiation of bacterial from viral infections. However, some of the novel parameters should be further evaluated in larger and better characterized cohorts of patients in order to find their clinical applications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
61
2
3

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 109 publications
(68 citation statements)
references
References 29 publications
2
61
2
3
Order By: Relevance
“…PCT has become a widely used marker in recent years. The superiority of PCT over CRP, WBC and neutrophil counts for predicting the bacterial etiology of infection was also shown in our previous study [5].…”
Section: Introductionsupporting
confidence: 73%
See 1 more Smart Citation
“…PCT has become a widely used marker in recent years. The superiority of PCT over CRP, WBC and neutrophil counts for predicting the bacterial etiology of infection was also shown in our previous study [5].…”
Section: Introductionsupporting
confidence: 73%
“…In the control group, 18 healthy adult persons were enrolled (5 females and 13 males) with a mean age 43 yrs spanning 23-69 yrs. The details describing the inclusion and exclusion criteria and clinical diagnostics have been reported elsewhere [5].…”
Section: Methodsmentioning
confidence: 99%
“…A possibility that UHBP might be secreted locally by activated neutrophils during APN is supported by these findings. First, levels of UHBP in the previous study by Kjolvmark et al and in this study were markedly elevated compared to serum HBP levels measured in patients with APN and urosepsis [3,8]. Second, in our study, levels of UHBP were positively correlated with the degree of pyuria.…”
Section: Discussionsupporting
confidence: 56%
“…Various bacterial infections, including APN and urosepsis, stimulate the release of HBP into the systemic circulation [10,3]. A recent study showed that urine HBP (UHBP) provided better sensitivity and specificity compared to urine dipstick analysis in children with upper or lower urinary tract infection (UTI) [8].…”
Section: Introductionmentioning
confidence: 99%
“…11 Also, the role of WBC in the prediction of a bacterial or viral origin is limited. 12,13 Absolute neutrophil count (ANC) performs better, but is still moderate. 12,13 Circulating immature granulocytes ('left shift') either as band count or _ENREF_8metamyelocyte, myelocyte and promyelocyte count (immature granulocytes count) as single diagnostic marker for an infection in the ICU is not (yet) supported by the few studies on this topic.…”
Section: Cellular Diagnostic Biomarkersmentioning
confidence: 99%